Metode Pendampingan Iman Anak melalui Kegiatan Serikat Kepausan Anak Misioner di Stasi Santo Yosef Kampung Baru - Theorodus Donni Tangel; Yohanes Yuda; Fabianus Sidi (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
This research aims to determine the forms of activities for mentoring children's faith, implementation of mentoring methods, supporting and inhibiting factors for mentoring children's faith through SEKAMI activities at Stasi St. Yosef Kampung Baru. A descriptive qualitative approach, with interactive analysis was used to analyze data collected through observation, interviews, with 13 informants consisting of 4 companions and 9 SEKAMI members. The results of this research show that the forms of mentoring activities are communicative, creative, communal and learning activities. Based on the mentoring methods, namely the explaining, asking, doing and assigning methods, it is known that the most dominant method used by the mentors is the doing method because this method is considered to be able to help children see the relevance and practical application of the mentoring material in everyday life. The explanation method shows an attempt to provide a direct explanation regarding the material to be studied. The questioning method is used to encourage participants to participate in learning by formulating relevant questions. Meanwhile, the assignment method shows an effort to involve children in tasks that can test their understanding and skills. The combination of these four methods is a holistic approach to mentoring. Through a variety of different methods, it can provide an interesting, enjoyable and effective faith mentoring experience.